Free UX testing tool: The LudoVico UX Machine for physiological sensor data recording, analysis, and visualization for user experience design experiments - Lugmayr, Artur; Bender, Stuart (2016)
The LudoVico UX Machine-A FREELY AVAILABLE SOFTWARE FOR USABILITY TESTING. Gathering and the interpretation of usability data is a rather challenging task. We implemented a new tool for recording, archiving, and interpreting sensor data from user-experience (UX) experiments. The tool is capable of handling any type of sensor data. The current version of the tool named "The LudoVico UX Machine" is contributed as freely available tool to the UX community. It shall assist user experience designers in managing their experimental data. The current version is capable of handling medical and biofeedback data, which can be archived, analyzed, and visualized. Future implementations will include generic sensor data via a plug-in concept, and provide data-analysis capability to get deeper insights into gathered data. The tool shall contribute with a new technology to support the interaction design process across applications: smart cities, smart living, smart interaction, urban informatics, health, sustainable living, audience response, or biofeedback. The tool will be made available in mid-2016 and can be found on: http://www.artur-lugmayr.com.